Analysis of two cases of myasthenic crisis - Kulczyński, Marcin; Sapko, Klaudia; Marciniec, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Myasthenia gravis is an autoimmune disease of the postsynaptic part of the neuromuscular junction. The disease is chronic, manifesting itself in the fatigue of various muscle groups, and the first manifestation of the disease often affects the muscles that move the eyeball and eyelid, although MG can lead to weakness of any muscle group. In turn, myasthenic crisis is a severe worsening of muscle weakness that often results in the urgent need of mechanical ventilation of the patient, due to the respiratory failure. Case reports: The first patient, 64 years old, female was admitted to the Neurology Department due to breathing difficulties and weakness of the limbs, which suddenly worsened within a dozen of hours before admission. During the stay, steroid therapy was used, as well as six times plasma exchange took place at the Nephrology Department with good treatment tolerance. The dosage of pyridostigmine was also modified, with no adverse effects. During the stay, the patient’s condition improved - respiratory disorders resolved, ptosis was significantly withdrawn, and limb muscle tension increased globally. The second patient, aged 67, also female, with a history of myasthenia gravis as well, was admitted to the Neurology Department due to increased fatigue, ptosis, dysphagia, and difficulties in speaking and breathing. Steroid therapy was used, but due to high blood glucose, the steroid dose was reduced and a 2-day cladribine treatment was initiated, with good tolerance. Discussion: Myasthenic crisis is often a life-threatening condition that requires immediate treatment. Steroid therapy, pyridostigmine, IVIG and plasma exchange are standard approaches in myasthenic crisis. Cladribine is not an ordinary approach, but can be beneficial in some patients.